GE_GERICHTE P/20842/2010 vom 7. November 2014 - GE Cour de justice (2014)
PRINCIPE DE L'ACCUSATION; FAUX INTELLECTUEL DANS LES TITRES; ESCROQUERIE; DOMMAGE; INDEMNITÉ(EN GÉNÉRAL); DOMMAGES-INTÉRÊTS | CPP.9.1; CPP.433; CPP.429; CP.251.1; CP.146; CO.41